ESTIMATION OF ABOVE GROUND CARBON STOCKS AT LAND-USE SYSTEM IN KUNINGAN REGENCY - Iing Nasihin; Dede Kosasih (Journal of Forestry And Environment, 2018)
Role vegetation in binding carbon happens on during photosynthesis process. Land-use change from vegetate land to non-vegetate will increase GHGs through carbon release to atmosphere. Kuningan Regency is upstream region for some region in below. This research aims for knowing land cover and land-use and above ground carbon stocks in the Kuningan Regency. Geographical Information System (GIS) and remote sensing were used to determine the changes based on date series of Landsat satellite imagery. Estimating total carbon stocks determined basis of the land cover and land-use spatial data. Typically aboveground carbon stock density (ton C ha-1) obtained from Directorate of Forest Resource Inventory and Monitoring (IPSDH) in 2015. The result showed that there was largest potential of above ground carbon stocks in Kuningan derived from mix garden and forest that contribute reached 4.81 million ton C or 91.67% of total carbon stock potential. Carbon stock from mix gardens reached 2.27 million ton C or 43.37 % and  2.53 million ton C form forest or 48.29% of the total potential carbon stock, covering primary forests  1.52 million tons C (28.98%), pine and teak plantations  813,058.76 ton C (15.49%) and 200,790.92 ton C (3.82%) respectively.Keywords : GIS, carbon stocks, land-use system